The Efforts Of The Indonesian Government In Overcoming Seed Smuggling Benur Lobsters Overseas - Fatihah Rizkiyah; Endro Legowo; Abdul Rivai Ras; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This article explains Indonesian government's efforts to overcome the smuggling of lobster seeds abroad. In explaining this issue, the writer uses the descriptive-qualitative method. The results of the discussion show that Indonesia continues to make efforts to stop smuggling lobster seeds or benur out of the country. The government has made various efforts to tackle the crime of smuggling lobster seeds through synergy with the Ministry of Maritime Affairs and Fisheries, the Navy, Air and Water Police, and Customs. The Ministry of Maritime Affairs and Fisheries is trying to eradicate lobster seed smuggling by launching four ships quickly for the perpetrators of lobster seed smuggling spread across Batam, Jambi, Kupang and Jakarta. The four ships were named Hiu Biru 01, Hiu Biru 02, Hiu Biru 03 and Hiu Biru 04. The Ministry of Maritime Affairs and Fisheries through the Director General of Capture Fisheries Circular Letter No.B.22891/DJPT/Pl.130/XI/2020 dated November 26, 2020 stopped the export of Lobster Benur Seeds. Air and Water Police Polri has also carried out various methods which are classified into two efforts, namely preventive and repressive efforts. Preventive efforts include providing assistance with fishing gear for lobster seed cultivation, patrols by the Water and Air Police Unit, socialization on the prohibition on catching and sending lobster seeds, and raids in territorial waters. Police repressive efforts by carrying out legal action, namely, making arrests and confiscations. In addition, the Indonesian Navy is assisting in synergy with the Ministry of Maritime Affairs and Fisheries in smuggling lobster seeds by strengthening supervision at points considered vulnerable on the sea lanes. In addition, the role of customs is in enforcing the law to prevent smuggling of lobster seeds in collaboration with internal customs and stakeholders. The success of the thwart of smuggling of lobster seeds was the result of the synergy carried out between the KKP, the Indonesian Navy, Customs, the Directorate of Water Police, and others so as to save the Indonesian state losses of up to billions of rupiah for the smuggling of lobster seeds.